Catastrophic Allergic Fungal Sinusitis: A Report of Two Cases. Issue 4 (December 2020) - Walter, Eyal; McKean, Erin L.; Camelo-Piragua, Sandra I.; Parmar, Hemant A.; Trobe, Jonathan D.
Abstract : Background: Allergic fungal rhinosinusitis (AFRS) is a common condition in which sinusitis develops as an IgE-mediated response to common sinonasal fungal organisms. If that response leads to blockage of sinus ostia, bone expansion and erosion by expansive cysts containing dense inspissated debris may occur with the potential for critical neurovascular compression including damage to the anterior visual pathway. Methods: Review of clinical and imaging features of 2 patients who sustained catastrophic clinical outcomes. Results: The first patient had pansinusitis with massive mucocele-like cysts expanding the sphenoid sinus and cranial base and causing compression of the anterior visual pathway that led to persistent severe vision loss despite extensive sinus surgery. The second patient developed sphenoethmoidal expansion with a marked inflammatory response and presumed conversion to invasive fungal sinusitis that caused anterior visual pathway vision loss, bilateral ocular motor palsies from extension into the cavernous sinuses, and death from a large middle cerebral artery stroke. Conclusions: Although AFRS is most often benign and treatable, it may rarely produce catastrophic outcomes, especially if the sphenoid sinus is involved. Irreversible vision loss may occur from compression, and ocular motor palsies and death from conversion to invasive fungal disease. Close ophthalmologic and imaging monitoring is necessary in patients with expanded sinuses, and prophylactic sinus surgery may be indicated in certain cases.